To watch from distance: an interactive film model based on Brechtian film theory - Cavus, Metin; Ozcan, Oguzhan (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2010)
With the emergence of new media, interactive film projects have mainly struggled to resolve the contradiction between dramatic structures and interaction. Dramatic film presents identification with the main character, where the viewer is constantly oppressed by the narrative, and therefore lost in illusion. In this context, when we bring on the scene interaction, the drama apparently starts to lose its power. In this article, a new interactive film model based on Brechtian film theory is proposed. This model presents a new way of spatiotemporal construction where different audiovisual combinations can be viewed successively, and this way the viewer can actively construct his/her own story. Theoretical framework of the Brechtian interactive film model is supported by an interactive film application, named Academia. The main feature of the model is that, while interaction is very simple, the continuity of the narrative is preserved and the film requiring an intellectual level of interpretation.
Keywords: interactive film; Brechtian film model; distanciating effect; spatial presentation; Art